Peningkatan Responsivitas Layanan Instalasi Gawat Darurat Melalui Penerapan Sistem Rekam Medis Elektronik Pendekatan Model Human, Organization and Technology-Fit - Hedie Kristiawan; Adi Anggoro Parulian; Bhisma Jaya Prakasa (Lontara Journal of Health Science and Technology, 2026)
The Emergency Department (ED) necessitates high responsiveness and precise data management to optimize patient care. This study aims to evaluate the effectiveness of Electronic Medical Record (EMR) implementation at the ED of RSUD dr. Slamet Garut using the HOT-Fit framework. The research utilized a mixed methods design with descriptive statistics to assess user perceptions among 49 medical staff members. Data analysis focused on the alignment of Human, Organization, and Technology factors alongside Net Benefits. The results showed that the majority of respondents held higher education degrees, supporting system adaptability. The evaluation indicated a “Very Good” performance level, with a Net Benefit score of 93.1% and strong organizational support (89.8%), although a minor gap in IT communication (1.6%) was identified. This study contributes empirically by emphasizing that ini critical environments like teh ED, organizational support is a determinant factor as crucial as techonological reliablitity for implementation success. It is concluded that the EMR implementation has achieved meaningful use, improving efficiency and service quality, though targeted training and better communication strategies are recommended for long term sustainability.